Performing the Digital : Performativity and Performance Studies in Digital Cultures - Martina Leeker; Imanuel Schipper; Timon Beyes (transcript, 2017)
How is performativity shaped by digital technologies – and how do performative practices reflect and alter techno-social formations?'Performing the Digital'explores, maps and theorizes the conditions and effects of performativity in digital cultures. Bringing together scholars from performance studies, media theory, sociology and organization studies as well as practitioners of performance, the contributions engage with the implications of digital media and its networked infrastructures for modulations of affect and the body, for performing cities, protest, organization and markets, and for the performativity of critique.With contributions by Marie-Luise Angerer, Timon Beyes, Scott deLahunta and Florian Jenett, Margarete Jahrmann, Susan Kozel, Ann-Christina Lange, Oliver Leistert, Martina Leeker, Jon McKenzie, Sigrid Merx, Melanie Mohren and Bernhard Herbordt, Imanuel Schipper and Jens Schröter.